Exploring the Evolution of Female Identity: A Case Study of Karina in Mobile Legends - Danny Susanto (Green Publisher Indonesia, 2024)
This study investigates the portrayal of female characters in the popular mobile game, Mobile Legends, focusing on the character Karina, and its implications for gender representation in the gaming industry and broader societal contexts. Drawing from feminist theories and semiotics by Roland Barthes, the research examines how Karina's characterization challenges or reinforces patriarchal norms within gaming narratives. The analysis delves into the appeal of Karina for both male and female players, exploring how her portrayal embodies a blend of masculine strength and feminine charm. Through the lens of feminist scholars such as Simone de Beauvoir and Spivak, the study evaluates whether Karina's depiction in Mobile Legends aligns with or counters traditional gender stereotypes, particularly regarding the perceived inferiority of women. Furthermore, the research examines the implications of Karina's characterization for players of different genders, considering how it reflects and potentially shapes broader societal attitudes towards gender roles and equality. Ultimately, the findings highlight the complex interplay between gender representation in gaming and societal perceptions, advocating for more inclusive and empowering portrayals of women in digital entertainment narratives.